Discovery and Exploration of the Efficient Acyclic Dehydration of Hexoses in Dimethyl Sulfoxide/Water. Issue 23 (18th November 2019) - Taarning, Esben; Sádaba, Irantzu; Jensen, Pernille Rose; Meier, Sebastian
Abstract: Current gaps in the development of sustainable processes include a lack of strategies to systematically identify and optimize the formation of new products. The dehydration of hexoses to 5‐hydroxymethylfurfural (HMF) is a particularly widely studied process. In an attempt to identify a new high‐selectivity conversion of glucose, quantitative NMR spectroscopy is used to screen conditions that have been reported to yield high conversions of glucose but low formation of HMF. In this manner, an olefinic six‐carbon byproduct is identified. By adding water, selectivity for the compound was nearly tripled relative to previous reports. The detection of high‐yielding side reactions in the formation of HMF is remarkable, considering how extensively HMF formation has been studied. High selectivity for the acyclic pathway allows hitherto unobserved intermediates in this pathway to be identified by using in situ NMR spectroscopy. An additional, presumably cyclic, pathway contributes to HMF formation. Abstract : Bringing 6 C back : The dehydration of hexoses to 5‐hydroxymethylfurfural (HMF) is a widely studied process. By using quantitative NMR spectroscopy to screen conditions that have been reported to yield high conversions of glucose but low formation of HMF, an olefinic six‐carbon byproduct is identified. By adding water, selectivity to this compound is significantly increased.